Short Communication: The prevalence and species of root-knot nematode which infect on potato seed in Central Java, Indonesia - MUTALA’LIAH MUTALA’LIAH; SIWI INDARTI; ARIF WIBOWO (Society for Indonesian Biodiversity, 2019)
Mutala’liah, Indarti S , Wibowo A. 2019. Short Communication: The prevalence and species of root-knot nematode which infect on potato seed in Central Java, Indonesia. Biodiversitas 20: 11-16. Root-knot nematodes are considered as one of the most destructive pathogens of potatoes, especially on tuber seed. Infected potato seed will cause tuber malformation and the most important thing is as the main spreading source of Meloidogyne spp. The objective of this research was to know the prevalence and identify the species of root-knot nematode which attack the potato seed in four sub-districts of potato production centre in Central Java, Indonesia. Molecular and morphological identification was conducted for the nematode species identification. PCR assay using MIG primer to detect three tropical root-knot nematodes followed by sequencing was conducted for molecular detection, while the perennial pattern was conducted for morphological detection. Results showed that root-knot nematodes on potato seed were generally distributed in Central Java with the prevalence percentage between 14.28-88.23% on the three from four sampling area. The molecular and morphological identification show that species of root-knot nematodes identified on potato seeds were Meloidogyne javanica, M. incognita, and M. arenaria.